Numerical investigation on thermal performance of thermoelectric-cooler integrated cold plate of thermal control liquid loop in spacecraft. (March 2023) - Gao, Li-Jun; Xu, Hui-Juan; Zhang, Xin; Wang, Ji-Xiang; Wang, Ao-Bing
Abstract: The traditional single-phase fluid loop (SFL) and traditioanl thermal control algorithm can barely control the temperature rapidly. Thermoelectric cooler (TEC) has been proved to be a good thermal controller because of its high reliability, liquid-free characteristics, and fast response. This paper proposes a TEC-based precooling module that resides in front of the cold plate (CP), and consists of a TEC-CP system, manifesting a high compatibility between the novel precooling module and traditional SFL. The TEC-CP system was designed, and a mathematical model of heat and mass transfer was developed to numerically investigate the effects of the geometric parameters, TEC operating conditions, and liquid cooling states of the precooling module upon payload thermal performance. Through analysis, an optimal TEC-based precooling module with optimal geometric dimensions was attained, where the coolant temperature was decreased by 13.04 K, resulting in a 28.98% reduction compared to that without the precooling module. Transient results also demonstrate that the temperature response time can be within 3 min, indicating a fast response system for temperature control. Results outlined in this paper provide structural and data references for future designs of scientific rack-level thermal control loops in space stations. Highlights: A novel thermoelectric-cooler (TEC)-based precooling module is proposed. It provides local rapid cooling capacity for traditional space thermal management. The precooling module is optimized in terms of thermal performance and COP. The COP of TEC is needed to be sacrificed to obtain the optimal cooling capacity. Compared with the traditional one, the focused temperature can be decreased by 28.98%.